First access to a mycolic acid-based bioorthogonal reporter for the study of the mycomembrane and mycoloyltransferases in Corynebacteria. Issue 87 (7th October 2019) - Lesur, Emilie; Baron, Aurélie; Dietrich, Christiane; Buchotte, Marie; Doisneau, Gilles; Urban, Dominique; Beau, Jean-Marie; Bayan, Nicolas; Vauzeilles, Boris; Guianvarc'h, Dominique; Bourdreux, Yann
Abstract : In this study we describe the first synthesis of an alkyne-based trehalose monomycolate probe closely mimicking the complex pattern of mycolic acids and its utility for the study of mycomembrane and mycoloyltransferases in Corynebacteria . Abstract : In this study, we report the first synthesis of an alkyne-based trehalose monomycolate probe containing a β-hydroxylated fatty acid and an α-branched chain similar to those of the natural mycolic acid. We demonstrate its utility for the labeling of the mycomembrane of Corynebacteria as well as for the study of mycoloyltransferases.